Effectiveness of Canva and AI-Generated Quran Story Videos on Tahfidz Students’ Reading Comprehension - Muh. Dimyati; Sa'dana Ainul (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study examined the effectiveness of Canva-based AI-generated Quran story videos in improving Fahmul Maqru' among female Tahfidz students at MA Al-Amiriyyah Banyuwangi. A quasi-experimental pre-test-post-test control group design was applied to 50 students, divided into experimental and control classes. Data were collected through comprehension tests and student questionnaires, then analyzed using the Shapiro-Wilk test, Mann-Whitney U test, Wilcoxon Signed Rank test, and N-gain calculation. The results showed that the experimental group achieved a significantly higher gain score than the control group (p < 0.001; d = 2.39), with an average N-gain of 0.79 in the high category. Students also responded positively to the media in terms of ease of use and attractiveness. The findings indicate that Canva-based visualization effectively supports reading comprehension by helping students connect Qur’anic narratives with deeper meaning in a digitally familiar learning environment. This study contributes to multimedia learning theory in Islamic education and offers a practical model for Tahfidz instruction.